The rigidity of the African State and its acceptance of western ideological invasion: An analysis of the Nigeria State. (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This paper examines the ongoing impact of colonial legacies on African states, focusing on the complexities of achieving true independence and the challenges posed by persistent Western influences. Despite gaining independence, many African nations continue to grapple with the remnants of colonial structures and ideologies, which were inherited rather than dismantled. The result of colonialism and post-colonial ideology by the Nigerian leaders is a social fabric which is overstrained and about to burst given the massive corruption, insecurities, religious and ethnic bigotry and economic rascality and policy summersault. These therefore, is a veritable Pandora's box of seriousproblems. The continuity of economic dependency and political instability is exacerbating underdevelopment. The paper highlights the failures of post-independence governance and education systems, which often perpetuate the same systems of oppression established during colonial rule. Colonialism was not merely a system of exploitation, but one whose essential purpose was to repatriate the profits to the so-called ‘mother’ country, and merely seeing Africa as only a geographical expression and landscape. The paper explores the diverse multicultural identity of African states, emphasizing the need to understand and embrace this diversity to overcome historical and contemporary challenges occasioned by colonial ideology. The paper adopts a theoretical approach by analysing Nigeria as a notable example in Africa, and underscores the importance of addressing both external legacies and internal issues to foster genuine self-determination and progress. The paper recommends that there should be national ideological reorientation programmes that will engender inclusive and transparent leadership that will dismantle this rigid colonial dependency and invasion of western ideology in the Nigerian State.
Keywords: African State Rigidity; Colonial Legacy; Multiculturalism; Economic Dependency; Educational System